2018
DOI: 10.1002/rmv.2024
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of acute viral respiratory infections common in Pakistan: A review

Abstract: Summary Respiratory infections, especially those of the lower respiratory tract, remain a foremost cause of mortality and morbidity of children greater than 5 years in developing countries including Pakistan. Ignoring these acute‐level infections may lead to complications. Particularly in Pakistan, respiratory infections account for 20% to 30% of all deaths of children. Even though these infections are common, insufficiency of accessible data hinders development of a comprehensive summary of the problem. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 21 publications
0
24
0
2
Order By: Relevance
“…Acute respiratory infections (ARIs) remain one of the most common major public health threats, accounting for millions of episodes of severe acute lower respiratory infections that result in hospital admissions of otherwise healthy infants and young children worldwide [1][2][3][4][5][6][7]. One-third of the annual deaths occurring in the world are thought to be due to infectious diseases, and respiratory tract infections are responsible for 4 million deaths worldwide each year [8].…”
Section: Introductionmentioning
confidence: 99%
“…Acute respiratory infections (ARIs) remain one of the most common major public health threats, accounting for millions of episodes of severe acute lower respiratory infections that result in hospital admissions of otherwise healthy infants and young children worldwide [1][2][3][4][5][6][7]. One-third of the annual deaths occurring in the world are thought to be due to infectious diseases, and respiratory tract infections are responsible for 4 million deaths worldwide each year [8].…”
Section: Introductionmentioning
confidence: 99%
“…Chest X-Ray shows local infiltrating shadows on the pulmonary lobes or infiltration around the hilar lung and peritracheal cuff sign. It is estimated that 4–16% of acute respiratory tract infections are caused by hMPV [ 27 , 28 ], which was first identified in 2001. In 2003, Runan et al [ 12 ] reported a case of hMPV infection in China, and other cases followed [ 13 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chest X-ray showed local in ltrating shadow of pulmonary lobes or in ltration around hilar lung and peritracheal cuff sign. It is estimated that 4-16% of acute respiratory tract infections are caused by hMPV [22,23]. The virus has attracted wide attention at home and abroad since it was rst identi ed in 2001.…”
Section: Discussionmentioning
confidence: 99%